Possible effects of the composite dark matter at the linear collider - Murakami Yuko; Sekiguchi Motoo; Wada Hiroaki; Wakayama Masayuki (EPJ Web of Conferences)
The existence of the dark matter is currently one of the strong motivations for beyond the standard model. We consider the model of the composite dark matter. Our model assumes that meson-like dark matter (call it dark mesons) is a bounded state of dark quark and anti-dark quark pairs, where they have a confining force at work. The confining force is based on the QCD-like hidden colour gauge theory. At the future linear collider, we can study the missing energy for the final state of our model.